Asthma in children and adolescents with type 1 diabetes in Germany and Austria: Frequency and metabolic control. Issue 4 (8th December 2017) - Hörtenhuber, Thomas; Kiess, Wieland; Fröhlich‐Reiterer, Elke; Raile, Klemens; Stachow, Rainer; Bollow, Esther; Rami‐Merhar, Birgit; Holl, Reinhard W.; ,
Abstract : Objective: To investigate the prevalence of asthma in young patients with type 1 diabetes mellitus (T1D) from Austria and Germany and its influence on their metabolic control. Methods: This prospective, multicenter observational cohort study was based on the DPV‐registry (German/Austrian DPV initiative) including 51 926 patients with T1D (<20 years). All clinical data were documented prospectively. To identify patients with additional asthma, the entry of the diagnosis asthma as well as asthma medication was used for classification. Results: 1755 patients (3.4%) of the cohort had the diagnosis asthma or received asthma‐specific drugs. Patients with asthma needed higher insulin doses (0.88 ± 0.3 vs 0.84 ± 0.3 U/kg, P  < .01) and had decreased height‐standard deviation score (SDS) (−0.002 ± 1.04 vs 0.085 ± 1.02, P  < .01); they were more often males (61% vs 52%, P  < .01), had an increased body mass index (BMI)‐SDS (0.31 ± 0.89 vs 0.28 ± 0.89, P  = .04) and experienced more severe hypoglycemia (4.5 [4.2; 4.8] vs 3.2 [3.2; 3.3] events/100 pts. years, P  < .01). Glycated hemoglobin A1c (HbA1c) did not differ between patients with and without asthma overall, only sub groups (corticosteroids vs leukotriene antagonist and corticosteroids vs sympatomimetics) revealed differences. No influence of asthma medication on metabolic control or BMI‐SDS could be found. Conclusion: In our DPV‐database, frequency of asthma and T1D seems similar to the prevalence of asthma in the healthy German background population. The concomitant diagnosis of asthma and T1D had minor influence on metabolic control and diabetes complication rate, although there was no difference in HbA1c overall. Patients with both diseases seem to be slightly growth restricted and require slightly higher insulin doses.